Correspondencia entre Antonio Pereira y Roberto H. Todd - Pedreira, Antonio S.; Todd, Roberto H. (My University, 1942)
Homicidio de José Pérez Moris.
Keywords: Pérez Moris, José; Masoneria--Puerto Rico.; Freemasonry--Puerto Rico.